2018
DOI: 10.1002/erv.2612
|View full text |Cite
|
Sign up to set email alerts
|

Childhood body mass index and development of eating disorder traits across adolescence

Abstract: Our results have implications for conceptualizing the interrelation of BMI and eating disorders across childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…In a recent study of 11‐ to 12‐year‐olds, we observed that overweight co‐occurred with DEBs (Larsen, Strandberg‐Larsen, Olsen, Micali, & Nybo Andersen, ). This is in line with increasing evidence showing that childhood overweight predicts later onset of DEBs (Forrester‐Knauss, Perren, & Alsaker, ; Micali et al, ; Munkholm et al, ; Neumark‐Sztainer et al, ; Neumark‐Sztainer, Paxton, Hannan, Haines, & Story, ; Reed, Micali, Bulik, Smith, & Wade, ; Stice, Presnell, & Spangler, ; Wiklund et al, ). However, not all research concurs; other studies report no association between childhood body mass index (BMI) and DEBs in early adolescence (Evans et al, ; Gardner, Stark, Friedman, & Jackson, ).…”
Section: Introductionsupporting
confidence: 86%
“…In a recent study of 11‐ to 12‐year‐olds, we observed that overweight co‐occurred with DEBs (Larsen, Strandberg‐Larsen, Olsen, Micali, & Nybo Andersen, ). This is in line with increasing evidence showing that childhood overweight predicts later onset of DEBs (Forrester‐Knauss, Perren, & Alsaker, ; Micali et al, ; Munkholm et al, ; Neumark‐Sztainer et al, ; Neumark‐Sztainer, Paxton, Hannan, Haines, & Story, ; Reed, Micali, Bulik, Smith, & Wade, ; Stice, Presnell, & Spangler, ; Wiklund et al, ). However, not all research concurs; other studies report no association between childhood body mass index (BMI) and DEBs in early adolescence (Evans et al, ; Gardner, Stark, Friedman, & Jackson, ).…”
Section: Introductionsupporting
confidence: 86%
“…Early adolescence is a time when pubertal maturation is prominently on view for others, can be quite varied in onset and presentation, and is often accompanied by weight gain. Just has been found for BMI (Brixval, Rayce, Rasmussen, Holstein, & Due, 2012; Fairburn, Welsh, Doll, Davies, & O'Connor, 1997; Gardner, Brown, & Boice, 2012; Helfert & Warschburger, 2013; Levinson et al, 2013; Wiklund et al, 2018), earlier (i.e., more advanced relative to peers) pubertal maturation has been associated with DE (e.g., Graber, Brooks-Gunn, Paikoff, & Warren, 1994; Haynos, Watts, Loth, Pearson, & Neumark-Stzainer, 2016; Levinson et al, 2013; for reviews see Ricciardelli & Yager, 2016; Striegel-Moore & Cachelin, 1999; Wiklund et al, 2018), appearance dissatisfaction and poorer body image (Rousseau, Rodgers, & Eggermont, 2017; Rosseau, Trekels, & Eggermont, 2018), appearance anxiety (Webb, Zimmer-Gembeck, & Mastro, 2016; Zimmer-Gembeck et al, 2018), and peer teasing or criticism about appearance (Rosseau et al, 2018; Zimmer-Gembeck et al, 2018).…”
Section: A Biopsychosocial Model and The Tripartite Sociocultural Influence Modelmentioning
confidence: 87%
“…36% of patients with severe restrictive disorders previously had a high and premorbid BMI. This suggests that obesity and overweight may be risk factors for subsequent ED (23,24) with an increased risk of late diagnosis (10 months later in our study) and the development of complications with a worse prognosis (6,25,26).…”
mentioning
confidence: 66%